New insights into the pathology of pulmonary hypertension: implication of the miR-210/ISCU1/2/Fe-S axis - Tang, Haiyang (EMBO Mol Med, 2015)
Elevated pulmonary arterial pressure in patients with pulmonary hypertension (PH) is mainly caused by increased pulmonary vascular resistance (PVR), due primarily to sustained pulmonary vasoconstriction and excessive pulmonary vascular remodeling. According to the current classification, PH has been classified into five categories based on etiology (Simonneau et al, 2013). Among them, group 1 or pulmonary arterial hypertension (PAH) is a rare but progressive and deadly disease affecting ∽1–10 per 1 million people. Despite expanding treatment options to ameliorate patients' symptoms, PAH remains a devastating disease with a poor long-term prognosis.